Perubahan Pola Belanja Masyarakat : Sebuah kajian di lingkungan masyarakat perkotaan - Maria Widyarini; Nina Septina (Business Administration Department - Universitas Katolik Parahyangan, 2009)
Everything is changing in this world. Including a buying pattern of the consumer,caused by one or other reasons. This article is focused on the changing of consumerselection for the shopping of their everyday needs in the urban area. The article discussedon factor that caused of shifting from the traditional market into a modernmarket. This based on research which were conducted in four different city duringseven weeks observations. The research was done through interview and focusgroups discussion, and found that the shift into a modern market were caused byfactors of location, price, promotion, facility provided. Meanwhile, some will stay intraditional market, because of some factors such as bargaining process, interpersonalrelationship, and variation of the product. Further research is needed to find a form ofcooperation among actors in the market and develop a positive image for both side.On the other hand, also need an involvement from the Government in socialization,implementation and evaluation of the regulation.Keywords: Consumer behavior, retail, modern market